The Impact of Capital Inflows on Economic Growth in Nigeria: Empirical Evidence from Wavelet Coherence Technique - Adebayo, Tomiwa Sunday (Asian Journal of Economics and Empirical Research, 2020)
The study explores the interaction between capital inflows and economic growth in Nigeria using data between 1981 and 2018. This study utilized the ARDL techniques to catch the short and long-run dynamics among variables utilized, and the granger causality test was utilized to ascertain the direction of causality. Furthermore, the wavelet coherence, a recent and more powerful technique was deployed to verify the co-movement and causality among the variables. Findings from the ARDL techniques depict; (i) there is cointegration among the variables in the long-run; (ii) Gross capital formation impact economic growth positively (iii) foreign aid and FDI inflows have an insignificant impact on economic growth. The Granger causality test reveals; (i) feedback causality between gross capital formation and economic growth; (ii) unidirectional causality was found running from FDI inflows and foreign aid to economic growth. The wavelet coherence provides supportive evidence for the ARDL and Granger causality test. Based on these findings, recommendations were suggested.